Grip strength – Agreement analysis between two dynamometers: JAMAR vs E-Link - Tomás, Maria Teresa (2012)
Introduction – Assessing grip strength has proved to be of vital importance because of its relationship with the functional capacity of individuals, in order to determine levels of risk for future disability and thereby establish prevention strategies. Most studies use the JAMAR Hydraulic dynamometer that provides the value of isometric force obtained during the performance of grip movement. However, there are other dynamometers available, such as portable computerized dynamometer E-Link (Biometrics), which provides the value of maximum force (peak force) in addition to other variables such as the rate of fatigue. There are no studies that allow us to accept or not and compare values ​​obtained with both devices and perhaps use them interchangeably. Purpose – To evaluate the agreement between the measurements of grip strength (peak force or maximum force in kg) obtained from two different devices (portable dynamometers): a computerized (E-Link, Biometrics) and a hydraulic (JAMAR). Methodology – 29 subjects (13H, 16M, 22 ± 7 years, 23.2 ± 3.3 kg/m2) were assessed on two consecutive days at the same time of day. The test position chosen was recommended by the American Association of Occupational Therapists and was considered the best result from three attempts for the dominant hand. A correlation was studied between values ​​obtained in the variable analyzed in each equipment (Spearman coefficient) and Bland-Altman analysis to assess the agreement between the two measurements. Results – The correlation coefficient between the two measurements was high (rs = 0,956, p <0.001) and Bland & Altman's analysis of the values ​​obtained are all within the range of mean±2SD. Conclusions – The two measurements were shown to be concordant, revealing that the tested dynamometers can be comparable or used interchangeably in different studies and populations.